Transfer Pricing Aggressiveness, Thin Capitalization, Political Connection, Tax Avoidance: Does Corporate Governance Have A Role in Indonesia? - Fasita, Eta; Firmansyah, Amrie; Irawan, Ferry (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study investigates the association of transfer pricing aggressiveness, thin capitalization, and political connection with tax avoidance and the corporate governance’s role in moderating these associations. The secondary data of this study are data and information obtained from financial reports and annual reports sourced from www.idx.co.id and www.idnfinancials.com. The analysis is conducted on 61 non-financial multinational companies listed on Indonesia Stock Exchange over the 2016-2019 period, chosen by the purposive sampling method resulting in 244 firm-year. Hypothesis testing employs regression analysis with a data panel. The result suggests that transfer pricing aggressiveness and political connection are negatively associated with tax avoidance. In contrast, thin capitalization is positively associated with tax avoidance. However, corporate governance can weaken each of these associations. This study indicates that the Indonesian Tax Authority should consider multinational companies with large interest debt structures on the list of priorities in tax inspection policy. Also, this study shows Indonesian firms are less likely to use political connection and transfer pricing to avoid tax.